Muslim women, agency and work: an exploration of Maqāṣid perspective - Subhani, Zulqernain Haider (IIUM Press, 2025)
This article presents an in-depth theoretical examination of women’s agency in the context of their participation in work through Maqāṣid al-Sharīꜥah, as articulated in contemporary Muslim scholarship. The concept of agency is critically analysed, highlighting the autonomy and capacity of women to make independent decisions, exert influence, and assert their authority across various life domains. Historical discourse on this subject within Islamic literature has been scarce, often overshadowed by intricate socio-cultural dynamics. However, a discernible shift has emerged in recent times, marked by the enlightened contributions of contemporary Muslim scholars who have offered profound insights into the constructs of women’s agency and their significant roles in work. The methodology of content analysis is utilized to integrate and critically assess ongoing scholarly conversations, thereby deepening the understanding of women’s agency and its expansive implications within socio-political and religious spheres. The study places particular emphasis on the intrinsic objectives of Sharīꜥah—namely, the promotion of humanity (al-Insāniyyah), dignity (al-Karāmah), freedom (al-Ḥurriyyah), justice (al-ꜥAdl) and equality (al-Musāwāt). By anchoring the discussion in the principles of Maqāṣid al-Sharīꜥah, this work delineates the pivotal role of agency in fostering the social, religious, and existential advancement of Muslim women, as well as in realizing the core objectives of Sharīꜥah while also demarcating the Islamic conceptualization of agency from feminist narratives